2019
DOI: 10.1099/acmi.ac2019.po0304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature increase in bacterial and fungal communities of chlorinated drinking water distribution systems

Abstract: Drinking Water Distribution Systems (DWDS) are diverse ecosystems where the majority of microorganisms live forming biofilms, which can alter the water quality if they are mobilised to the bulk water. Biofilm communities can be affected by the increase of temperature due to climate change, thus compromise the distribution of safe water. To understand the effect of temperature on biofilms in DWDS, biofilm was developed for 30 days at 16 °C and 24 °C using a full-scale experimental DWDS facility. Samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hallam et al (2001) found that biofilm activity was approximately 50% lower at a temperature of 7°C than at 17°C. In a recent study, differences in both bacterial and fungal community compositions at two different temperatures (16°C and 24°C) were observed at family level (Preciado et al, 2019). In conclusion, temperature can regulate various reactions within DWDS.…”
Section: Introductionmentioning
confidence: 82%
“…Hallam et al (2001) found that biofilm activity was approximately 50% lower at a temperature of 7°C than at 17°C. In a recent study, differences in both bacterial and fungal community compositions at two different temperatures (16°C and 24°C) were observed at family level (Preciado et al, 2019). In conclusion, temperature can regulate various reactions within DWDS.…”
Section: Introductionmentioning
confidence: 82%
“…Factors such as nutrient concentration, temperature and pH determine microbial community structure and potential for regrowth within DWDSs. Consequently, changes in temperature in DWDSs can influence microbial community composition, promoting the presence of pathogens and the potential for microbial regrowth, particularly of biofilms in the pipe environment [29,46]. A temperature increase of drinking water can influence the microbial ecology of DWDSs, affecting parameters such as potential growth (e.g., colony count at 22 • C, bacteria of the coli group and Legionella) and the presence of undesirable microorganisms because of their possible role in disease [29].…”
Section: Consequences Of Higher Temperatures and Legislationmentioning
confidence: 99%
“…However, publications about microorganisms in water supplies in many cases do not provide accurate data on water temperature [47]. It has been shown in a chlorinated DWDS in the UK that a rise of temperature from the average 16 • C in the warmer months to a temperature of 24 • C promoted changes and loss in the complexity of microbial biofilm communities [46].…”
Section: Consequences Of Higher Temperatures and Legislationmentioning
confidence: 99%
“…Previous studies in DWDS have shown that raw water quality and temperature can affect bacterial community characteristics in treated water including bacterial community composition, activity and abundance (G. Liu et al, 2013;Prest et al, 2016). Temperature can affect bacterial community composition (Preciado et al, 2019), by providing advantages to those species more competitive under higher temperatures (Prest et al, 2016). Donlan et al, (1994), showed that at warm temperatures in drinking water systems (15-25°C), biofilm accumulation rate increases, and this is associated with lowered disinfectant concentration and increased bulk water cell numbers.…”
Section: Temperature As a Potential Factormentioning
confidence: 99%
“…Changes in water organoleptic characteristics during distribution have also been associated to compounds leaching from plastic pipes, formation of disinfection by-products, metals originating from corroded pipes and biofilm metabolites (Zhou et al, 2017). In Mediterranean regions, distributed water temperatures are higher than the average range in Europe of between 3 and 25°C (Niquette et al, 2001;Preciado et al, 2019). Increased water temperatures can increase microbial growth and activity, potentially aggravating odour and taste problems whilst also selecting for different community compositions (Prest et al, 2016).…”
Section: Introductionmentioning
confidence: 99%